Artificial black holes (World Scientific, 2002)
Physicists are pondering on the possibility of simulating black holes in the laboratory by means of various "analogue models". These analogue models, typically based on condensed matter physics, can be used to help us understand general relativity (Einstein's gravity); conversely, abstract techniques developed in general relativity can sometimes be used to help us understand certain aspects of condensed matter physics. This text contains 13 chapters - written by experts in general relativity, particle physics and condensed matter physics - that explore various aspects of this two-way traffic.